IMPLEMENTASI MEDIA VIDEO ANIMASI DALAM PEMBELAJARAN IPAS UNTUK MENDORONG KEAKTIFAN BELAJAR SISWA KELAS III SD N 2 BUNUTIN KABUPATEN BANGLI TAHUN PELAJARAN 2025/2026 - Ni Wayan Widiantari; I Nyoman Sueca; Gusti Ayu Agung Reisa Mahendradhani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of animated video media in IPAS learning is important to encourage the learning activeness of elementary school students. The use of animated video media is able to create an interesting, interactive, and enjoyable learning atmosphere so that students become more active in participating in the learning process. The problems in this study are: (1) teachers’ strategies in using animated video media in the classroom, (2) the impact of using animated video media on students’ learning activeness, and (3) the obstacles faced by teachers in implementing animated video media in class III of SD Negeri 2 Bunutin. This study used a descriptive qualitative approach with the research subjects consisting of the principal, teachers, and third grade students of SD Negeri 2 Bunutin. Data collection techniques used observation, interviews, and documentation, which were then analyzed descriptively and qualitatively. The theories used in this study include: (1) Constructivism Theory, (2) Behavioristic Theory, and (3) TPACK Theory. The results of the study indicate that: (1) the teacher’s strategy in using animated video media was carried out by displaying videos that were appropriate to the IPAS material, inviting students to discuss, asking questions, and actively involving students in the learning process, (2) the use of animated video media had a positive impact on students’ learning activeness such as increasing attention, enthusiasm, courage to ask questions, answer questions, and student involvement in the learning process, and (3) the obstacles faced by teachers included limited facilities and infrastructure, technological readiness, classroom management, and limited learning time.